Recyclable magnetic nanocomposites for efficient removal of cadmium ions from water: performance, mechanism and isotherm studies. Issue 1 (31st December 2023) - Melhi, Saad
ABSTRACT: Herein, succinic acid functionalized Fe3 O4 @AMPA nanocomposite was synthesized as an effective adsorbent and used for the efficient removal of Cd(II) ions from aqueous media. Zeta potential, BET, TEM, TGA, and FTIR spectra were applied to characterize the Fe3 O4 @AMPA@SA nanocomposite. According to the BET analysis, the surface area of Fe3 O4 @AMPA@SA was found to be 43 m 2 /g. The influence of pH value, initial Cd(II) concentration, adsorbent dosage, temperature, and contact time on the adsorption process was achieved via the batch experiment method. The result showed that the optimal parameters were 6, 250 mg/L, 0.03 g/50 mL, 150 min, and 25°C, respectively. The experimental data fitted well to the Langmuir isotherm and the pseudo-first-order models. The maximum monolayer adsorption capacity of Cd(II) ions was 265 mg g −1 . The adsorption mechanism of Cd(II) on magnetic nanocomposite is physical adsorption. The Fe3 O4 @AMPA@SA nanocomposite shows excellent reusability with a removal efficiency of 81.4% after three cycles. GRAPHICAL ABSTRACT: uf0001